Intramucosal Calprotectin Expression in Inflammatory Bowel Disease (IBD) and Non-IBD Colorectal Inflammation - Krisnuhoni, Ening; Rini Handjari, Diah; Stephanie, Marini; Kencana, Lydia; Rahadiani, Nur (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Inflammatory bowel disease (IBD) diagnosis remains a challenge accompanied with high numbers of misdiagnosis causing suboptimal management. Tons of trials have been conducted to improve the diagnostic accuracy, one of which is the use of biomarker such as calprotectin. Calprotectin can be detected in tissue (intramucosal) and is becoming a potential marker of IBD. AIM: This study aims to determine intramucosal calprotectin expression in IBD, non-IBD colitis, and control. METHODS: This analytic retrospective study included consecutively sampled IBD and non-IBD colitis colorectal biopsy specimens, and control group obtained from Cipto Mangunkusumo Hospital registered from 2017 to 2019. Cases were included in the study if specimens were indicative of IBD and non-IBD clinically and histopathologically and no abnormality were found histopathologically in the control group. Specimens with non-adequate data from the hospital medical records or with missing tissue slides were excluded from the study. Calprotectin immunostaining was conducted to evaluate mean intramucosal calprotectin expression (cell/HPF) in each group. RESULTS: Most of the samples from IBD and non-IBD group (45 samples each) showed mild active inflammation. Mucosal calprotectin expression in aforementioned groups was higher than that of control group (p < 0.001). Subjects with active inflammation showed higher calprotectin expression compared to those with inactive inflammation (p < 0.001). Calprotectin expression was also related to activity grade. CONCLUSION: Higher calprotectin expression showed significant association with the presence of inflammation and disease activity. However, the application of intramucosal calprotectin immunohistochemistry test to determine inflammatory etiology (IBD vs. non-IBD) still needs to be further evaluated.